Sleep disorder at high altitude - Kong, F. (Sleep Medicine in Clinical Neurology, 2019)
In this chapter, we discuss the occurrence, mechanism, clinical manifestations, outcomes, and managements of a commonly encountered sleep disorder of someone traveling in high altitude for working and sight-seeing. Humans ascending to altitudes above 2500 m usually suffer from substantial disturbances in sleep quality as difficulty in sleep onset, frequent awakenings, respiratory disturbance, and a feeling of drowsiness on the next day. Data obtained from polysomnographic studies demonstrated several variations of sleep architecture in those healthy subjects ascending to high altitude during sleep, including periodic breathing and decreased non-rapid eye movement deep sleep stage 3 and 4 (in new nomenclature N3), which were usually accompanied by and the lowered arterial O2 and restricted ventilation. Hypoxia is most severe during sleep and in correspondence to periodic breathing and sleep disturbance at high altitude. Poor sleep quality impairs cognition and executive abilities at high altitude though it may largely be improved after full time of acclimatization. Evidence-based choices for clinicians to treat sleep disorder at high altitude are relatively scarce at present. Supplemental oxygen and dietary nitrate are effective in alleviating nocturnal hypoxia. There is strong evidence supporting the efficacy and safety of acetazolamide and nonbenzodiazepines in minimizing periodic breathing and improving sleep quality at high altitude. Keywords: sleep architecture, sleep disorder, sleep quality, periodic breathing,